Case report of superior mesenteric artery syndrome that developed in a lean type 2 diabetes patient and was associated with rapid body weight loss after sodium–glucose cotransporter 2 inhibitor administration. Issue 5 (27th February 2020) - Hirai, Taro; Kitada, Munehiro; Hayashi, Yoshihiro; Monno, Itaru; Takagaki, Yuta; Shimada, Keiji; Ogura, Yoshio; Fujii, Mizue; Konishi, Kazunori; Nakagawa, Atsushi; Koya, Daisuke
Abstract: A 58‐year‐old women who was diagnosed with type 2 diabetes 20 years earlier had been treated with antidiabetic medicines since she was aged 40 years. After sodium–glucose cotransporter 2 inhibitors administration, her bodyweight rapidly decreased from 40 to 30 kg over a period of 3 weeks. She had abdominal symptoms, including nausea, especially after a meal. On admission, physical examinations and laboratory data showed euglycemic ketoacidosis, dehydration and low insulin secretion levels. Additionally, abdominal contrast computed tomography showed the finding of superior mesenteric artery syndrome. This case urges caution, including rapid excessive bodyweight loss and euglycemic ketoacidosis, on the use of sodium–glucose cotransporter 2 for lean diabetes patients. Abstract : Administration of sodium–glucose cotransporter 2 inhibitors in a lean type 2 diabetes patient with insulinopenia promoted rapid excessive bodyweight loss through both energy loss into the urine and increased β‐oxidation. Rapid excessive bodyweight loss resulted in the development of superior mesenteric artery syndrome, and loss of dietary intake induced by superior mesenteric artery syndrome led to euglycemic ketosis and dehydration.